The Development of Teacher’s Social Competence in Rural Mountain Elementary School - Varetska, Olena (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
This paper attempted to illuminate the importance of social competence for elementary school teacher in rural mountain environment. The author analyzes the essential features, social and pedagogical challenges in rural schools, sensible changes characteristic of the modern village. Special attention is paid to the rural mountain school as a center of educational and social activities, its peculiarities and factors causing them, including the effect of mountain environment, climatic conditions, administration method, traditions, etc. It’s pointed out that teachers are also exposed to the effect of mountain environment. They work under tough weather conditions, often in a closed team, in the atmosphere of professional, social, economic and political information scarcity, which leads to a rapid “aging”, gradual professional, social decline and social competence development recession. The author proves the need to consider the environmental impact in the design of modern school, the need for innovative processes while maintaining the national spirit and the environment; the development of social competence of elementary school teacher in constantly changing social rural mountain environment is in the focus of attention.